Outcome Measures Used in Ocular Gene Therapy Trials: A Scoping Review of Current Practice - Jolly, Jasleen K.; Bridge, Holly; MacLaren, Robert E. (Frontiers in Pharmacology, 2019)
Multiple gene therapy trials are occurring for a variety of ophthalmic diseases around the world. The safety of gene therapy in the eye has been established and the next step is to reliably assess efficacy. This is primarily done through the use of imaging techniques and visual function measures. Standardised visual function assessments, however, were originally developed for a clinical setting and may not be suitable for detecting and quantifying therapeutic changes. This scoping review takes a comprehensive look at current practice in terms of the outcome measures defined at trial registration. These were compared to the outcome measures reported in the literature. All published trials reported the pre-registered primary outcome measure. A range of additional secondary outcomes were reported that were not originally planned. Gaps in gene therapy assessment exist and further discussion is required to find a way forward, particularly as more conditions progress to phase 2 and 3 trials. Several factors impacting on trial design and outcome measure choice are discussed.